Outcome measurement in speech and language therapy: a digital journey. Issue 1 (7th May 2020) - Moyse, Kathryn; Enderby, Pamela; Chadd, Katie; Gadhok, Kamini; Bedwell, Mark; Guest, Patrick
Abstract : Background: Evidencing the impact of speech and language therapy interventions is challenging. The UK's professional body for speech and language therapists (SLTs) is supporting a consistent approach to outcome measurement and analysis using Therapy Outcome Measures (TOMs). Objective: To develop a digital solution for collecting TOMs data, evaluate the impact of therapeutic interventions and explore contributing factors to outcome variation across clinical areas. Method: Agile methodology was applied to software development. Organisations were recruited to provide data. Criteria were identified to exemplify outcome variability. Results: A digital tool was developed. 21 organisations provided data on 16 356 individuals. Improvement in at least one domain of TOMs occurred in 77.1% of instances. Data for two clinical areas exemplify the tool's effectiveness in highlighting the impact of speech and language therapy. Conclusion: This established outcomes data set can be used to evaluate the impact of speech and language therapy, and explore variation in outcomes.